Inflammatory Gene Expression Profile and Defective Interferon‐γ and Granzyme K in Natural Killer Cells From Systemic Juvenile Idiopathic Arthritis Patients. Issue 1 (28th December 2016) - Put, Karen; Vandenhaute, Jessica; Avau, Anneleen; van Nieuwenhuijze, Annemarie; Brisse, Ellen; Dierckx, Tim; Rutgeerts, Omer; Garcia‐Perez, Josselyn E.; Toelen, Jaan; Waer, Mark; Leclercq, Georges; Goris, An; et al.
Abstract : Objective: Systemic juvenile idiopathic arthritis (JIA) is an immunoinflammatory disease characterized by arthritis and systemic manifestations. The role of natural killer (NK) cells in the pathogenesis of systemic JIA remains unclear. The purpose of this study was to perform a comprehensive analysis of NK cell phenotype and functionality in patients with systemic JIA. Methods: Transcriptional alterations specific to NK cells were investigated by RNA sequencing of highly purified NK cells from 6 patients with active systemic JIA and 6 age‐matched healthy controls. Cytokines (NK cell–stimulating and others) were quantified in plasma samples (n = 18). NK cell phenotype and cytotoxic activity against tumor cells were determined (n = 10), together with their interferon‐γ (IFNγ)–producing function (n = 8). Results: NK cells from the systemic JIA patients showed an altered gene expression profile compared to cells from the healthy controls, with enrichment of immunoinflammatory pathways, increased expression of innate genes including TLR4 and S100A9, and decreased expression of immune‐regulating genes such as IL10RA and GZMK . In the patients' plasma, interleukin‐18 (IL‐18) levels were increased, and a decreased ratio of IFNγ to IL‐18 was observed. NK cells from the patients exhibited specific alterations in the balance of inhibitory and activating receptors, with decreased killer cell lectin‐like receptor G1 and increased NKp44 expression. Although NK cells from the patients showed increased granzyme B expression, consistent with intact cytotoxicity and degranulation against a tumor cell line, decreased granzyme K expression in CD56 bright NK cells and defective IL‐18–induced IFNγ production and signaling were demonstrated. Conclusion: NK cells are active players in the inflammatory environment typical of systemic JIA. Although their cytotoxic function is globally intact, subtle defects in NK‐related pathways, such as granzyme K expression and IL‐18–driven IFNγ production, may contribute to the immunoinflammatory dysregulation in this disease.